The Personal Diary as a Space for Literary Thought in Four Authors from the Hispanic Context: Ribeyro, Levrero, Piglia and and Trapiello - Luque Amo, Álvaro (2022)
This article studies the literary diaries of four authors: Julio Ramón Ribeyro (Peru), Mario Levrero (Uruguay), Ricardo Piglia (Argentina) and Andrés Trapiello (Spain), with the aim of analyzing the role that writing linked to literary reflection, criticism and commentary played in these texts. A joint perspective of these works allows us to understand the relevance of metaliterary writing in the configuration of the personal diaries published from the last decades of the twentieth century onwards in the Hispanic context. This thematic aspect strengthens two crucial aspects of the diaries : on the one hand, it reaffirms their literary entity; on the other hand, it gives the personal diary a series of qualities as a critical-literary tool that the diarist uses for different purposes.